Experimenting with concepts from modular product design and multi-objective optimization to benefit people living in poverty. (2017) - Wasley, Nicholas S.; Lewis, Patrick K.; Mattson, Christopher A.; Ottosson, Hans J.
Abstract: Every discipline has its own specific knowledge that has been accumulated and refined over time. In the aerospace industry, for example, the domain knowledge of multidisciplinary optimization has grown and matured. The same has happened with domain knowledge related to modularity in the consumer product design industry. Knowledge from these domains has carried over to other domains such as automotive, medical, and defense, and has enabled advances in these disciplines. One domain that has been underserved by the advanced engineering methodologies coming from other disciplines is the domain of design for the developing world . Exploring the use of engineering domain knowledge to alleviate poverty is a valuable study that will open opportunities to use engineering to benefit resource poor individuals. This paper explores the domain knowledge of modularity and multi-objective optimization and applies it to the domain of design for the developing world by introducing the concept of collaborative products to assist the resource poor individuals. Can knowledge from one domain be used in a new domain, and if so, what would it look like? In this paper, a general methodology is presented, followed by a simple example to illustrate the design of a collaborative product for the developing world. The paper suggests that by using domain knowledge from a non-related domain paired with the method presented, products can be designed and optimized for collaborative performance with potential to both generate new income and save money for the end customers.